О видах рода тетрамеза - Tetramesa Walk. (Hymenoptera, Eurytomidae) - фауны Украины - Зерова, М.Д. (Вестник зоологии, 1967)
The article deals with the data on spreading, biology and taxonomy of 40 species of Tetramesa W al k, in the Ukrainian fauna. The list of the Tetramesa species fodder crops includes 39 species of Graminaea of the Ukrainian flora. As a result of comparative-morphological study of Tetramesa species their unification into six subgenus groups is suggested. This unification is based on the concepts of Eurytomidae evolution (in particular, Harmolitinae) set forth in the researches of R. Bugbee (1936) and M. N. Nikolskaya (1956).